Real-world pharmacovigilance investigation of imipenem/cilastatin: signal detection using the FDA Adverse Event Reporting System (FAERS) database - Jia, Peng; Zhou, Yusen; Gao, Yuan; Wang, Shangyu; Yin, Jiangliu; Lian, Yixiang; Lai, Quanyou (Frontiers in Pharmacology, 2025)
BackgroundAlthough imipenem/cilastatin (IMI/CIL) has demonstrated favorable therapeutic efficacy against various infections, the incidence of potential adverse events (AEs) has escalated in parallel with its increased utilization and has been documented in clinical trials. However, a comprehensive understanding of real-world implications remains lacking.MethodsBy conducting a comprehensive search in the FDA Adverse Event Reporting System (FAERS) database, AE reports associated with IMI/CIL as the primary suspect (PS) were selected for analysis, spanning from the first quarter of 2004 to the fourth quarter of 2023. Utilizing disproportionality analysis techniques, potential signals of AE s were identified through reported odds ratio (ROR), proportional report ratio (PRR), Bayesian confidence propagation neural network (BCPNN), and empirical Bayesian geometric mean (EBGM). The obtained results were systematically classified using Medical Dictionary for Regulatory Activities (MedDRA).ResultFrom the first quarter of 2004 to the fourth quarter of 2023, a total of 2,574 reports documenting AEs associated with IMI/CIL were obtained, with more than half (n = 1,517, 58.94%) involving individuals aged over 60 years old. Descriptive analysis was conducted based on age groups and time to onset, revealing that the majority of AEs occurred within 3 days. Adverse drug reactions caused by IMI/CIL were classified into 24 system organ classes (SOCs) at the preferred term (PT) level. Furthermore, previously unreported and clinically significant AEs such as cerebral atrophy, and delirium were also identified at the PT level.ConclusionThis study offers a more comprehensive insight into the monitoring, supervision, and management of adverse drug reactions associated with IMI/CIL. Clinicians should pay further attention to the implications of numerous AEs and their corresponding signal intensities, as well as unrecorded signals of severe AEs. This holds significant value in enhancing the clinical safety profile of IMI/CIL.